A Contrastive Analysis of Haplology Patterns in Modern Standard English and Modern Standard Arabic - Abd Ali Nayif Hasan (Universitas Sanata Dharma, 2020)
Phonologically speaking, each word in a language consists of one or more syllables. In both modern standard English (henceforth MSE) and modern standard Arabic (henceforth MSA), a syllable may be followed by an identical one. In this case, one of such syllables is eliminated. This phonological process is referred to as haplology. The present study aims at finding out similarities and differences of haplology patterns between MSE and MSA. Accordingly, a comparison of haplology patterns between such two languages has been conducted. This phonological phenomenon results in the fact that differences are more than similarities of such patterns between both languages. Additionally, it appears that all eliminated syllables in MSE consist of onset and centre without coda and that they occur only in a medial position. As far as MSA is concerned, all elided syllables consist of onset and centre except the syllables [?it] and [zil] which consist of onset, centre and coda, and the syllables [un],[an] and [in] which consist of a centre and coda without onset. Some of such syllables can occur initially, others medially and that most of them occur finally. Such results lead to the conclusions that haplology patterns are mentioned to make pronunciation easy and that elision of some syllables in certain contexts investigates musical rhythm.